RESPONSES OF PHYTOHORMONES, CARBON AND NITROGEN STATUS TO THE TRUNK-EXTENSION PRUNING IN THREE-YEAR-OLD PAULOWNIA PLANTATION - Y. Zhao; £; Y. Feng; £; P. Sun; B. Wang; J. Qiao; W. Duan; J. Zhang; H. Zhou; C. Yang (Journal of Animal and Plant Sciences, 2020)
Trunk-extension pruning is often used to promote sprouting of latent buds, and therefore extend the vertical growth of the main trunk in young Paulownia plantation in China. However, the biological basis for the technique remains unclear. In this study, we applied two pruning treatments and a control to 120 and 108 three-year-old Paulownia trees in 2015 and 2016, respectively. We observed the latent buds sprouting in 2015, and found that the number of individuals of first sprouting/total number of individuals and number of sprouted buds/total number of sprouted buds both exceeded 50% from 18 to 24 days after pruning.We collected phloem samples from the top of the stem at 7, 14, 21, and 28 d after the pruning in 2016. We then analyzed phytohormones, total C and N, reduced sugar and free amino acid contents of the samples. Results showed that pruning significantly reduced the contents of abscisic acid (ABA) and indole-3-acetic acid (IAA), especially on day 21 as compared with control. This was coincided with the sprouting of latent buds in the two pruned treatments. Therefore reduced IAA, ABA contents in pruned trees promoted the sprouting of latent buds. Our results provide a biological basis for extending the main trunk height.
Keywords: Trunk-extension pruning; Latent buds; Phytohormones; Carbon; Nitrogen; Paulownia plantation